2020
DOI: 10.12691/nnr-6-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Inorganic Nanoparticles for the Detection of Food and Waterborne Bacterial Pathogens

Abstract: Infections acquired from ingesting contaminated food and water poses an adverse effect on public health and safety, thus affecting nations' economy. Technical approaches developed over years have contributed adequately to microbial detection in food and water, yet, unveiling spaces for more improvement on early and rapid detection of pathogens. This review highlights different strategy assessing bio-functionalized inorganic nanoparticles towards the detection of pathogens in food and water samples. Conjugates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 104 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Electrochemical biosensor ideas come from the basic of glucose biosensors. Electrochemical biosensor detect the responses (current) at a constant potential during electrochemical reaction [27]. With the features of high sensitivity, low cost and rapid response makes it the best choice for both qualitative and quantitative analytes detection [28].…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…Electrochemical biosensor ideas come from the basic of glucose biosensors. Electrochemical biosensor detect the responses (current) at a constant potential during electrochemical reaction [27]. With the features of high sensitivity, low cost and rapid response makes it the best choice for both qualitative and quantitative analytes detection [28].…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…Recent advances in colorimetric and plasmonic sensing of food and waterborne pathogens have been achieved due to the incorporation of the nanotechnology approach into biosensors [18]. This technique demonstrates the importance of visual colour change as a robust tool for the detection of food and waterborne pathogens in a fast manner [19]. For example, Wu et al devised aptamer-coated gold nanoparticles (AuNPs) and assessed the conjugate for colorimetric and plasmonic detection of Salmonella and E. coli O157:H7 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such include; Escherichia coli (Duan et al, 2020), Salmonella typhi (Yi et al, 2019), Salmonella enteritidis (Alamer et al, 2018), Staphylococcus aureus (Du et al, 2020), Vibrio cholera (Peng and Chen, 2019), Vibrio parahaemolyticus (Sun et al, 2019), Bacillus cereus (Li et al, 2018), Listeria monocytogenes (Zhang L. et al, 2016), Shigella flexneri (Feng et al, 2019), Pseudomonas aeruginosa (Das et al, 2019), Campylobacter jejuni (Alamer et al, 2018), and Group A Streptococcus pyogenes (Eryılmaz et al, 2020). A review by Daramola et al (2020) reported traditional-based (plate culture), immunological-based (ELISA), nucleic acid-based (PCR, Sequencing), and protein-based (MALDI-TOF-MS) methods as veritable techniques for the detection of pathogenic bacteria. However, limitations which include longer detection time, limited trained personnel, and the use of expensive and sophisticated materials have constantly challenged the relevance of these widely used methods (Daramola et al, 2020;Ferone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A review by Daramola et al (2020) reported traditional-based (plate culture), immunological-based (ELISA), nucleic acid-based (PCR, Sequencing), and protein-based (MALDI-TOF-MS) methods as veritable techniques for the detection of pathogenic bacteria. However, limitations which include longer detection time, limited trained personnel, and the use of expensive and sophisticated materials have constantly challenged the relevance of these widely used methods (Daramola et al, 2020;Ferone et al, 2020). In recent times, nanotechnology-biosensor-based techniques have received global attention with growing interest in optical biosensors namely; surface plasmon resonance (SPR), photographic and colorimetric detection (Yoo and Lee, 2016;Mocan et al, 2017;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation